Reconstruction of craniofacial bone defects with autologous human bone marrow stem cells and autogenous bone grafts: A case report with review of literature - Prasanth P Panicker; Sunil Paramel Mohan; Jaisanghar Nallusamy; Suman J Lakshmi; Joseph Johny; Manoj K Bhaskaran (Wolters Kluwer Medknow Publications, 2020)
Reconstruction of craniofacial bony defects has always been a challenging task for the surgeons over the years. The science of reconstructing such defects is of at most importance to craniofacial and plastic surgeons due to its relevance in facial aesthetics function as well as prerequisite procedure for continuing other surgical procedures. The main goal of the reconstruction of the craniofacial defects is to reduce the morbidity by restoring the facial form and aesthetics, as well as a good function of the facial structures by achieving a reasonable occlusion and articulation. Although significant improvements have occurred during the last few decades, challenges still exist as to what type of reconstruction to be carried out with regard to techniques and the type and quality of materials of choice to be used. As decades progressed, the advancement in surgical techniques and the variety of reconstruction methods have definitely improved the quality of life. This article reviews the method of bony reconstruction of craniofacial defects using autologous human bone marrow stem cells and autologous bone grafts and its modification, which includes much recent tissue engineering techniques and regenerative medicine, thereby replacing older techniques by biological substitutes, which can restore improve and maintain orofacial function and aesthetics.